The Function of Dramatic Persona in the Film “The Menu” (2022) - Munawaroh, Silvi; Heriyati, Nungki (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
This study aims to determine the portrayal of characters in the film The Menu 2022. In examining the characters in the film, The Menu, researcher conducted a characterization analysis which was classified into seven functions of dramatic characters through the theoretical framework of Vladimir Propp. This study is used because narratology theory can focus on the actions of a character who is limited in terms of meaning. Through this classification, researchers can find out the depiction of characters and the limits of their actions. The data collection method is carried out by qualitative methods and narrative analysis by collecting research results in the form of descriptions accompanied by screenshots. This study produced findings in the form of depictions of seven-character functions contained in the film